REFORMASI ADMINISTRASI PELAYANAN PUBLIK: STUDI PADA PENERAPAN KEBIJAKAN ELECTRONIC SAMSAT (E-SAMSAT) DI PROVINSI DKI JAKARTA - Arfah Habib Saragih; Neni Susilawati; Adang Hendrawan (Magister Administrasi Publik, FISIP, 2019)
One indicator of the success of an administrative reform of public services is the quality of good public services. There are various ways that can be taken to improve the quality of public services, including by implementing the Electronic Samsat (E-Samsat) policy by the DKI Jakarta Province with the aim of improving services to the public in addition to increasing local tax revenues from motor vehicle tax. This study uses descriptive qualitative research methods with in-depth interviews and observations. The results of the study show that the process of implementing E-Samsat policy has not been effective and efficient. Some of the causes include: there is still a lack of E-Samsat socialization to the community, there are still many people who use intermediary services for motor vehicle tax payments, and E-Samsat is not yet a full online system. The implication of this finding is to recommend to the government that it should be able to improve the E-Samsat to become a full online system and improve the socialization of E-Samsat to the public.